PENGARUH DOW JONES ISLAMIC MARKET INDEX DAN DAMPAK MAKROEKONOMI TERHADAP INDEKS SAHAM SYARIAH INDONESIA - Shanfariza Nevada; Rohmawati Kusumaningtias (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2020)
This research aims to to identify the effect of the Dow Jones Islamic Market Index and the macroeconomic impact (global commodity prices of palm oil, coal, gold and nickel) on the Indonesian Sharia Stock Index. This study uses secondary data in the form of the movement of the Dow Jones Islamic Asia Pacific Index (DJIAP), the Indonesian Sharia Stock Index and global commodity prices (palm oil, coal, gold and nickel) for the period 2014-2019 with a total of 61 samples. Through SPSS statistical data analysis, it shows that partially the price of palm oil and gold commodities has a significant effect on the Indonesian Syariah Stock Index. And partially DJIAP, coal commodity prices and nickel commodity prices do not affect the Indonesian Syariah Stock Index. Whereas the Dow Jones Islamic Market Index simultaneously and the macroeconomic impact affect the Indonesian Sharia Stock Index.